The advertisement call of the treefrog Nyctimantis rugiceps Boulenger, 1882 (Anura: Hylidae), with notes on its natural history and toxicity - de Souza, Camila Camargo; Rivera-Correa, Mauricio; Padial, Jose M.; Castroviejo-Fisher, Santiago (Zootaxa, 2018)
Nyctimantis rugiceps Boulenger, 1882 (Fig. 1A) is a Neotropical treefrog (Duellman & Trueb 1976; Faivovich et al. 2005) known only from disjunct localities in Amazonian Colombia, Ecuador, and Peru (Pérez-Villota et al. 2009). This species has the skin of the skull co-ossified and reproduces—including calling behavior, egg deposition and tadpole development—in water-filled tree or bamboo cavities (Duellman & Trueb 1976; Duellman 1978). Given its secretive behavior, this is a poorly known species and, as noted by Duellman (1978: 169), “the major clue to the life history of Nyctimantis is the calling behavior of the males”. Unfortunately, the only quantitative description of the advertisement call of N. rugiceps is a brief passage in Duellman (1978) based on four specimens from Santa Cecilia, Ecuador, where important variables are missing (e.g., call duration). More importantly, graphs illustrating the waveform and spectrogram are missing. Considering these limitations and the importance of advertisement calls to the study of anurans (Köhler et al. 2017), we provide a quantitative description using a call recording obtained in Leticia, Amazonas, Colombia.